2014
DOI: 10.1177/0022034514538451
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Antibodies to Oral Microorganisms and Hyperglycemia in Adults

Abstract: We conducted a cross-sectional analysis to evaluate the relationship between serum antibody titers against 19 selected oral microorganisms and measures of hyperglycemia in a large, nationally representative data set. The study population consisted of 7,848 participants from the National Health and Nutrition Examination Survey III (1988-1994) who were at least 40 yrs old, with complete serum IgG antibody data against 19 oral microorganisms. The 19 antibody titers were grouped into 4 categories via cluster analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…The authors identified the following four mutually exclusive clusters and named them using the commonly used color coding for periodontal bacteria (39): i) orange-blue ( Eubacterium nodatum, Actinomyces naeslundii ), ii) yellow-orange ( Streptococcus intermedius, Streptococcus oralis, Streptococcus mutans, Fusobacterium nucleatum, Parvimonas micros (previously Micromonas micros), Capnocytophaga ochracea ), iii) red-green ( Tannerella forsythia, Treponema denticola, Aggregatibacter actinomycetemcomitans mix, Eikenella corrodens, Selenomonas noxia, Veillonella parvula, Campylobacter rectus ), and iv) orange-red ( Prevotella melaninogenica, Prevotella intermedia, Prevotella nigrescens, Porphyromonas gingivalis mix ) clusters (38). Cluster scores were created from the sum of the natural log transformed values of antibody levels for each species in the cluster to form continuous measures.…”
Section: Methodsmentioning
confidence: 99%
“…The authors identified the following four mutually exclusive clusters and named them using the commonly used color coding for periodontal bacteria (39): i) orange-blue ( Eubacterium nodatum, Actinomyces naeslundii ), ii) yellow-orange ( Streptococcus intermedius, Streptococcus oralis, Streptococcus mutans, Fusobacterium nucleatum, Parvimonas micros (previously Micromonas micros), Capnocytophaga ochracea ), iii) red-green ( Tannerella forsythia, Treponema denticola, Aggregatibacter actinomycetemcomitans mix, Eikenella corrodens, Selenomonas noxia, Veillonella parvula, Campylobacter rectus ), and iv) orange-red ( Prevotella melaninogenica, Prevotella intermedia, Prevotella nigrescens, Porphyromonas gingivalis mix ) clusters (38). Cluster scores were created from the sum of the natural log transformed values of antibody levels for each species in the cluster to form continuous measures.…”
Section: Methodsmentioning
confidence: 99%
“…We classified antibody clusters using serum IgG antibody titer values among NHANES III participants . Briefly, each of the 19 serum IgG antibody titer values were natural log transformed and standardized by dividing by the log transformed population standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…The cluster scores were calculated for every participant. The outcomes were the sum of the z‐scores for each of the clusters …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations